Improving Activity and Learning Outcomes by Using JIGSAW Type with Algebraic Tiles Props - Abdul Waris (Universitas Islam Jember, 2017)
The purpose of the research to describe the using of JIGSAW type with algebra paving for increasing the mathematical students activities and to describe the using of JIGSAW type with algebra paving for increasing the mathematicl students learning outcomes. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIII at MTs Nurul Hikmah. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: JIGSAW, students’ activity, learning outcomes, algebra paving